The economics of government spending: an institutional approach - Mlilo, Mthokozisi (My University, 2019)
This thesis investigates the role of institutional quality on the impact of government expenditure on economic performance. The thesis consists of five chapters. Chapter 1 provides an introduction of the thesis. Chapters 2, 3 and 4 are empirical chapters examining the role of institutions on the relationship between government expenditure and various indicators of economic performance. Chapter 5 concludes by giving policy recommendations. In chapter 1 we provide a background, motivation, objectives, hypothesis to be tested, gaps in the literature, contributions of the study and the main findings. In chapter 2 we explore how institutional quality affects the government spending-output growth nexus. We estimate a modified growth accounting model found in Hansson and Henrekson (1994) and control for institutional quality by employing panel regression techniques on a panel of 71 countries over a period 1970-2015. Our main estimation technique, 3SLS with seemingly unrelated errors, is able to control for endogeneity and cross equation correlation. We find that the institutional quality variable has a mitigating effect on the relationship between government expenditure and output growth however, government expenditure generally has a negative and detrimental effect on output growth. This suggests that better institutional quality offsets the adverse effects of government expenditure. As such, there is a need to come up with policies that strengthen institutional quality and enhance the effectiveness of government expenditure programs. Chapter 3 we examine the role of institutions on the optimal size of the government. The quadratic method of Armey (1995) and Scully (1994) method are employed on the country (time series regression) and group (panel data regression) estimations. Furthermore, we use the Hansen (1999) panel threshold regression technique to determine the presence of an optimal size and the values thereof. We ascertain that the majority of countries do have a significant optimal size of government. However, we note that the optimal size of government varies across countries and regions. Despite the presence of a non-linear relationship between government expenditure and output growth, there seems to be a marked difference between the size of government across levels of development and institutional arrangements. Countries with better institutions and higher levels of development seem to have a lower optimal level of government size. Perhaps, better institutions and higher levels of development help mitigate the adverse effects of government expenditure on output growth through the minimisation of the scope and scale of government activities, i.e., government size. Chapter 4 investigates the Twin Deficits Hypothesis (TWDH) and the role of institutional quality on a sample of 48 countries for the period 1995-2013. Using the national income accounting decomposition and the approaches in Feldstein and Horioka (1980) and Fidrmuc (2003) we investigate the role of institutional quality and capital mobility on the current account deficits and the government budget deficits (i.e., TWDH) nexus. We apply OLS, fixed effects, random effects regressions and panel cointegration techniques in our analysis. The results from the panel cointegration tests show that a long run relationship exists between the current account balance, investment and the government budget balance. The results reveal that current account deficits are mainly driven by private investment flows. However, we only find support for the Twin Deficits Hypothesis in a sample of developed countries and higher institutional quality countries. The results imply that governments of these countries enjoy financing from international sources and can easily finance their budget deficits without siphoning domestic savings away from investment. This result is unsurprising considering that capital seems to flow towards areas with perceived less risk. This suggests that current account deficits in developing countries are as a result of private agents’ decisions and not driven by government budget deficits.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, in the Faculty of Commerce, Law and Management, School of Economic and Business Sciences. 27 March 2019
Keywords: Government spending policy--South Africa; South Africa--Economic conditions